Prevalence and Patterns of Sugar-Sweetened Beverage Consumption in Canadian Youth: A Northern Focus - Davis, Laura E.; Davison, Colleen M. (ARCTIC, 2017)
Regular consumption of sugar-sweetened beverages (SSBs) is a well-known risk factor for weight gain, tooth decay, and metabolic syndrome. Rates of SSB consumption in Nunavut specifically, have been noted to be exceptionally high. This study describes consumption rates of specific foods and beverages, with a focus on SSBs, among adolescents in Nunavut, northern Canada as a whole, and the Canadian provinces, using data from the 2010 and 2014 cycles of the Health Behaviour in School-aged Children (HBSC) study to investigate population characteristics and consumption patterns. Comparative analyses of consumption patterns for Nunavut, the three territories combined, and the southern provinces found that in 2010, those who consumed SSBs once a day or more comprised 53.1% of adolescents in Nunavut, 31.1% in the northern territories and 24% in the provinces. Comparable figures for 2014 were 55.0% in Nunavut, but only 27.0% in all the territories, and 19.1% in the provinces. The percentage of adolescents who consumed fruit and vegetables daily was also lower in Nunavut than in the provinces (65.5% vs. 85.3% in 2010, and 57.5% vs. 84.4% in 2014). More Nunavut adolescents consumed sweets and potato chips daily than provincial adolescents (42.6% vs. 27.6% in 2010, and 52.2% vs. 25.2% in 2014). A greater proportion of Nunavut adolescents reported high consumption of SSBs, as well as other energy-dense foods, when compared to adolescents in the three territories combined and in the provinces. These results confirm previous studies but provide a current and comprehensive analysis that can help inform future food and nutrition priorities and programing. La consommation régulière de boissons édulcorées est un facteur de risque bien connu pour le gain de poids, les caries et le syndrome métabolique. Au Nunavut plus particulièrement, la consommation de boissons édulcorées est exceptionnellement élevée. Cette étude décrit les taux de consommation d’aliments et de boissons spécifiques et met l’accent sur les boissons édulcorées ...